A 7-Week Summer Camp in Antarctica Induces Fluctuations on Human Oral Microbiome, Pro-Inflammatory Markers and Metabolic Hormones Profile - Moraes, Michele M.; Mendes, Thiago T.; Borges, Leandro; Nuñez Espinosa, Cristian Andrés; Nunez-Espinosa, Cristian; Goncalves, Dawit A. P.; Simoes, Carolina B.; Vieira, Tales S.; Ladeira, Roberto V. P.; Lourenco, Talita G. B.; Ribeiro, Danielle V.; Hatanaka, Elaine; et al. (My University, 2023)
Antarctic camps pose psychophysiological challenges related to isolated, confined, and extreme (ICE) conditions, including meals composed of sealed food. ICE conditions can influence the microbiome and inflammatory responses. Seven expeditioners took part in a 7-week Antarctic summer camp (Nelson Island) and were evaluated at Pre-Camp (i.e., at the beginning of the ship travel), Camp-Initial (i.e., 4th and 5th day in camp), Camp-Middle (i.e., 19th-20th, and 33rd-34th days), Camp-Final (i.e., 45th-46th day), and at the Post-Camp (on the ship). At the Pre-Camp, Camp-Initial, and Camp-Final, we assessed microbiome and inflammatory markers. Catecholamines were accessed Pre- and Post-Camp. Heart rate variability (HRV), leptin, thyroid stimulating hormone (TSH), and thyroxine (T4) were accessed at all time points. Students' t-tests or repeated-measures analysis of variance (one or two-way ANOVA) followed by Student-Newman-Keuls (post hoc) were used for parametric analysis. Kruskal-Wallis test was applied for non-parametric analysis. Microbiome analysis showed a predominance of Pseudomonadota (34.01%), Bacillota (29.82%), and Bacteroidota (18.54%), followed by Actinomycetota (5.85%), and Fusobacteria (5.74%). Staying in a long-term Antarctic camp resulted in microbiome fluctuations with a reduction in Pseudomonadota-a "microbial signature" of disease. However, the pro-inflammatory marker leptin and IL-8 tended to increase, and the angiogenic factor VEGF was reduced during camp. These results suggest that distinct Antarctic natural environments and behavioral factors modulate oral microbiome and inflammation.
Keywords: catecholamines; cytokines; human microbiome phyla; inflammation; markers; oral microbiome; polar; stress-related responses